2017
DOI: 10.1002/ejhf.937
|View full text |Cite
|
Sign up to set email alerts
|

Similar clinical benefits from below‐target and target dose enalapril in patients with heart failure in the SOLVD Treatment trial

Abstract: In patients with HFrEF, the clinical benefits of ACE inhibitors appear to be similar at both below-target and target doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…It should also be highlighted that other subgroups such as men/women, diabetes/no-diabetes, ACEi/ARB . Differently from ACEi/ARBs and -blockers in which randomized trials compared different doses of these drugs, [21][22][23][24][25][26] no trials have compared different MRA doses. So far, the best available evidence comes from the EMPHASIS-HF trial, where patients were stratified to different eplerenone or placebo doses according to renal function.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be highlighted that other subgroups such as men/women, diabetes/no-diabetes, ACEi/ARB . Differently from ACEi/ARBs and -blockers in which randomized trials compared different doses of these drugs, [21][22][23][24][25][26] no trials have compared different MRA doses. So far, the best available evidence comes from the EMPHASIS-HF trial, where patients were stratified to different eplerenone or placebo doses according to renal function.…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed in the CONSENSUS study already that in the period examined the administration of enalapril in the case of 253 patients suffering from NYHA IV heart failure reduced the development of SCD by 27% (CONSENSUS Trial Study Group, 1987). In the SOLVD study examining 2569 patients Lam et al found that the administration of 20 mg enalapril per day reduced overall mortality by 12% and cardiovascular mortality by 4% in the case of heart failure patients (Lam et al, 2018). In the SAVE trial on 2,231 patients the administration of 3x25 mg captopril daily reduced overall cardiovascular mortality by a few percent compared to the placebo group but it did not meaningfully affect the risk of sudden cardiac death (Pfeffer et al, 1992).…”
Section: Long-term Treatment After Aborted Cardiac Deathmentioning
confidence: 99%
“…The SOLVD trial was designed to achieve and test enalapril (20 mg daily) vs. placebo, but at the end of the study the mean enalapril dose was only 11 mg daily and more than half of the patients enrolled failed to reach the target dose of the study drug. Thus, in this issue of the Journal, Lam et al . hypothesize that the beneficial effects of enalapril in the SOLVD trial may not depend on the dose achieved, and report a post‐hoc analysis of this trial assessing the associations between below‐target (5–10 mg daily) vs. target dose (20 mg daily) enalapril and outcomes in patients with HFrEF.…”
Section: High Vs Low Enalapril Doses In the Solvd Trialmentioning
confidence: 99%
“…The SOLVD trial was designed to achieve and test enalapril (20 mg daily) vs. placebo, but at the end of the study the mean enalapril dose was only 11 mg daily and more than half of the patients enrolled failed to reach the target dose of the study drug. Thus, in this issue of the Journal, Lam et al 13 hypothesize that the beneficial effects of enalapril in the SOLVD trial may not depend on the dose achieved, and report a post-hoc analysis of this trial assessing the associations between below-target (5-10 mg daily) vs. target dose (20 mg daily) enalapril and outcomes in patients with HFrEF. In particular, they show that both target dose enalapril vs. target dose placebo and below-target enalapril vs. below-target placebo achieved a reduction in the risk of all-cause mortality by 10% (absolute risk reduction of 5%), and of HF hospitalization (by 30% and 21%, respectively), leading to a reduction in the risk of the composite of mortality and HF hospitalization (by 30% and 22%, respectively).…”
Section: High Vs Low Enalapril Doses In the Solvd Trialmentioning
confidence: 99%